9 THE EFFICACY OF CONGENITAL ADRENAL HYPERPLASIA SCREENING IN CALIFORNIA. (1st January 2006) - Fang, P.; Banerjee, S.
Abstract : Background: Congenital adrenal hyperplasia (CAH) is a congenital condition that could lead to serious adverse outcome in the newborn period if not detected early. In June 2005, California became the 40th state to add CAH to its screening panel. Because of the lack of uniformity in the methodology and cutoff values used among the states, it is necessary to investigate whether California's Phase I CAH screening is effective in identifying the positive CAH cases with its current protocol. The objective of this study was to determine the efficacy of CAH screening in California. Method: 23 newborns with initial positive CAH screening results were included in the study. Newborns were grouped based on final diagnoses: 21 newborns were CAH negative and 2 newborns were identified as CAH positive. The false-positive rate of the CAH screening test was used as a marker for test efficacy. Result: 21 newborns were born prematurely and were diagnosed to be CAH negative. The correlation between birth weights and initial 17-hydroxyprogesterone (17-OHP) levels was -0.4512 ( p = .0401) while the correlation between gestational ages and initial 17-OHP levels was -0.3648 ( p = .1499). However, there was no correlation between age at collection and initial 17-OHP levels ( r = -.0054, p = .9815). California's CAH screening false-positive rate was 0.14%. Conclusion: Birth weight is a better predictor for initial 17-OHP levels than gestational age California's false-positive rate is comparable to those of other states that have CAH in their newborn screening panel. However, California may be able to further reduce its false-positive rate by adjusting the cutoff values for the low birth weight category